2007
DOI: 10.1002/mrdd.20140
|View full text |Cite
|
Sign up to set email alerts
|

Language and communicative development in Williams syndrome

Abstract: Williams syndrome, a genetic disorder caused by a microdeletion of approximately 25 genes on chromosome 7q11.23, is associated with mild to moderate intellectual disability or learning difficulties. Most individuals with Williams syndrome evidence a cognitive profile including relative strengths in verbal short-term memory and language, and considerable weakness in visuospatial construction. The syndrome has often been argued to provide strong evidence for the independence of language from other aspects of cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 78 publications
2
124
1
6
Order By: Relevance
“…Similar differences between DS and FXS have been reported for expressive syntax. The DS profile also appears to differ from that observed in WS, which is characterized by special weaknesses in visual-spatial ability and relative strengths in vocabulary and syntax [Mervis et al, , 2007Laws and Bishop, 2004].…”
Section: Syntactic Developmentmentioning
confidence: 85%
“…Similar differences between DS and FXS have been reported for expressive syntax. The DS profile also appears to differ from that observed in WS, which is characterized by special weaknesses in visual-spatial ability and relative strengths in vocabulary and syntax [Mervis et al, , 2007Laws and Bishop, 2004].…”
Section: Syntactic Developmentmentioning
confidence: 85%
“…Recent studies have reported positively selected genes for mental activity and/ or brain development in the human lineage: Abnormal spindle-like microcephaly associated and Microcephalin in relation to brain size (ASPM, Zhang 2003;MCPH1, Evans et al 2004;Wang and Su 2004, but see Currat et al 2006;Yuet al 2007); Dopamine receptor D4 and Monoamine oxidase A in relation to emotional activity (DRD4, Ding et al 2002;MAOA, Gilad et al 2002); Forkhead box P2 in relation to language (FOXP2, Enard et al 2002;Zhang et al 2002); and Spinocerebellar ataxia type 2 and Pituitary adenylate cyclase-activating polypeptide in relation to neurodegenerative disorders (SCA2, Yu et al 2005; PACAP, Wang et al 2005). In addition, many causal genes for several types of mental retardation, possibly related to brain and cognitive development, have recently been reported (Inlow and Restifo 2004;Mervis and Becerra 2007;Schumacher et al 2007). These genes are further thought to influence mental activity.…”
mentioning
confidence: 99%
“…Although the most prevalent mental disability in the syndrome is Attention Deficit Hyperactivity Disorder, the behavioral and emotional phenotype of individuals with Williams Syndrome is characterized by other affective problems, such as Generalized Anxiety Disorder, phobias, fears and social withdrawal (Martens et al, 2008;Mervis & Becerra, 2007;Leyfer et al 2006;Martens et al, 2008). Previous studies that used behavior problems assessment scales verified the prevalence of behavioral indicators of depression, almost always associated with anxiety and somatic complaints (Pérez-García, et al, 2011).…”
Section: Williams Syndromementioning
confidence: 95%